Effect of natural fibers-epoxy composite as thermal insulation coating on galvalume roof - Redi Bintarto; Anindito Purnowidodo; Djarot B. Darmadi; Teguh Dwi Widodo (Composites Part C: Open Access)
Natural fibre composite coatings are an excellent choice for developing and improving the properties of galvalume roofs. This study examines the impact of natural fibre coatings combined with epoxy on galvalume roofs in reducing the thermal conductivity of the roofing material, which in turn will decrease room temperature. Data were collected by applying a mixture of natural fibres and epoxy on top of galvalume roofs, then measuring the temperature around and inside a small room with dimensions of 50 cm x 50 cm. The roof type was varied using natural fibres, including Pandanus tectorius, Fimbristylis globulosa, pineapple leaf (Ananas comosus), and banana fronds (Musa paradisiaca). In addition to thermal conductivity testing, temperature measurements inside and around the room were conducted, along with temperature tests using a thermal imaging camera. The study shows that adding natural fibre mixed with banana fronds on galvalume roofs can reduce the highest thermal conductivity value by 8.88 W/m °C. Banana fronds also demonstrated the highest capability to lower room temperature by 3.2 °C. The study concludes that natural fibres can reduce thermal conductivity in roofs and lower room temperatures.